Перші знахідки Phaeobotryon negundinis (Ascomycota, Fungi) в Україні - Дука, А.В. (Київ : Інститут ботаніки ім. М.Г. Холодного НАН України, 2021)
Re-identification of old herbarium specimens, labeled as Sphaeropsis clintonii Peck, from the CWU (Myc) collection showed that they belong to the recently described species Phaeobotryon negundinis Daranag., Bulgakov & K.D. Hyde
Duka A.V. First finds of Phaeobotryon negundinis (Ascomycota, Fungi) in Ukraine
Keywords: fungi; biodiversity; new records; Ukraine